(untitled) (Marketing Journal, 2026)
Abstract This article analyzed the importance of cooperation between universities and industrial enterprises in training qualified personnel for the green economy. The study examined the mechanisms of green workforce training, modernization of educationalprograms, implementation of innovative educational technologies, and the use of international experience. The university-industry cooperation model was considered an important factor in improving the quality of education, introducing research results into production, and developing studentsʼ practical skills. The findings showed that the integration of education and industry contributes to the preparation of competitive specialists who meet the requirements of the green economy. The study also demonstrated that such cooperation plays a significant role in promoting innovative technologies and ensuring environmental sustainability. Keywords: green personnel, sustainable development, university-industrial cooperation, ecology, innovative technologies.